Responder analysis of a randomized comparison of the 13.3 mg/24 h and 9.5 mg/24 h rivastigmine patch - Molinuevo, José L.; Frölich, Lutz (Alzheimer's research & therapy, 2015)
Introduction: OPtimizing Transdermal Exelon In Mild-to-moderate Alzheimer’s disease (OPTIMA) was a randomized, double-blind comparison of 13.3 mg/24 h versus 9.5 mg/24 h rivastigmine patch in patients with mild-to-moderate Alzheimer’s disease who declined despite open-label treatment with 9.5 mg/24 h patch. Over 48 weeks of double-blind treatment, high-dose patch produced greater functional and cognitive benefits compared with 9.5 mg/24 h patch. Methods: Using OPTIMA data, a post-hoc responder analysis was performed to firstly, compare the proportion of patients demonstrating improvement or absence of decline with 13.3 mg/24 h versus 9.5 mg/24 h patch; and secondly, identify predictors of improvement or absence of decline. ‘Improvers’ were patients who improved on the Alzheimer’s Disease Assessment Scale–cognitive subscale (ADAS-cog) by ≥4 points from baseline, and did not decline on the instrumental domain of the Alzheimer’s Disease Cooperative Study–Activities of Daily Living scale (ADCS-IADL). ‘Non-decliners’ were patients who did not decline on either scale. Results: Overall, 265 patients randomized to 13.3 mg/24 h and 271 to 9.5 mg/24 h patch met the criteria for inclusion in the intention-to-treat population and were included in the analyses. Significantly more patients were ‘improvers’ with 13.3 mg/24 h compared with 9.5 mg/24 h patch at Weeks 24 (44 (16.6%) versus 19 (7.0%); P < 0.001) and 48 (21 (7.9%) versus 10 (3.7%); P = 0.023). A significantly greater proportion of patients were ‘non-decliners’ with 13.3 mg/24 h compared with 9.5 mg/24 h patch at Week 24 (71 (26.8%) versus 44 (16.2%); P = 0.002). At Week 48, there was a trend in favor of 13.3 mg/24 h patch. Functional and cognitive assessment scores at double-blind baseline did not consistently predict effects at Weeks 24 or 48. Conclusion: More patients with mild-to-moderate Alzheimer’s disease who are titrated to 13.3 mg/24 h rivastigmine patch at time of decline are ‘improvers’ or ‘non-decliners’ i.e. show responses on cognition and activities of daily living compared with patients remaining on 9.5 mg/24 h patch.